Aislamiento de Candida albicans de hisopado nasal y faríngeo en alumnos de secundaria - Huamán Reyes, Ana M. (2014)
Objective: To determine the presence of Candida albicans in throat and nasal secretion in high school students. Design: Cross-sectional study. Setting: Institute of Tropical Medicine, Universidad Nacional Mayor de San Marcos, Lima, Peru. Participants: High school students from San Juan Macias School in Santa Anita, Lima, Peru. Interventions: Nasal and throat samples were collected from 102 14-17 year-old students. Samples were grown on sabouraud agar and Candida CHROMOagar and identified by chlamydospores study and metabolic tests. Main outcome measures: Identification of C. albicans yeast. Results: Candida yeast was isolated from 11 students (10.8%). A significant percentage of yeast (36.4%) developed moderate resistance to fluconazole. Conclusions: Continuous surveillance of medically important yeasts in nasopharyngeal carriers is suggested in order to be prepared for eventual infectious conditions.